2021
DOI: 10.1177/0741932521996071
|View full text |Cite
|
Sign up to set email alerts
|

Equating and Assigning Targets in the Adapted Alternating Treatments Design: Review of Special Education Journals

Abstract: The current review examined the prevalence of the adapted alternating treatments design (AATD) across 22 special education journals and methods to equate and assign target sets to experimental conditions in the AATD. Since the seminal description of the design in 1985, a total of 49 articles were published using the AATD across 12 of the reviewed journals. The most prominent methods of equating target sets differed from prior reviews of behavior-analytic journals, likely due to the preponderance of response ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Thus, the experimenter conducted an internet search to find words of greater difficulty. The assignment of each word was done in a quasirandomized fashion that was identical to the target identification process used in Wong et al (2021) and was based on the best practices of equating targets reported by Cariveau et al (2021). The inclusion criteria for the target sight words included a) four‐syllable words (for Patrick and Katie) and one‐syllable words (for William), b) each four‐syllable word contained 9‐12 letters and each one‐syllable word contained four letters, c) no two words that were phonetically or visually similar were presented in the same instructional session, and d) no two words with the same initial letter were presented in the same instructional session.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the experimenter conducted an internet search to find words of greater difficulty. The assignment of each word was done in a quasirandomized fashion that was identical to the target identification process used in Wong et al (2021) and was based on the best practices of equating targets reported by Cariveau et al (2021). The inclusion criteria for the target sight words included a) four‐syllable words (for Patrick and Katie) and one‐syllable words (for William), b) each four‐syllable word contained 9‐12 letters and each one‐syllable word contained four letters, c) no two words that were phonetically or visually similar were presented in the same instructional session, and d) no two words with the same initial letter were presented in the same instructional session.…”
Section: Methodsmentioning
confidence: 99%
“…The assignment of unique, but equally difficult, targets across conditions is the defining characteristic of the AATD (Holcombe et al, 1994;Sindelar et al, 1985;Wolery et al, 2018), but also introduces an additional threat to internal validity if targets are not properly equated (Cariveau et al, 2020(Cariveau et al, , 2021. Cariveau et al (2020Cariveau et al ( , 2021 recently reviewed methods to equate and assign targets to conditions in published articles that used the AATD.…”
Section: Introductionmentioning
confidence: 99%
“…The assignment of unique, but equally difficult, targets across conditions is the defining characteristic of the AATD (Holcombe et al, 1994;Sindelar et al, 1985;Wolery et al, 2018), but also introduces an additional threat to internal validity if targets are not properly equated (Cariveau et al, 2020(Cariveau et al, , 2021. Cariveau et al (2020Cariveau et al ( , 2021 recently reviewed methods to equate and assign targets to conditions in published articles that used the AATD. The systematic and explicit equating of target stimuli, termed logical analysis by Sindelar et al (1985), was described in just over half of the studies in the behavior analytic (Cariveau et al, 2020;55.4%) and special education (Cariveau et al, 2021;65.3%) journals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations